Strategic Planning in Developing the Quality of Educators and Education Personnel - Hanif Al Kadri; Widiawati Widiawati (Indonesian Research Journal in Education |IRJE|, 2020)
Educators and educational personnel as the key actors in education who have a direct effect on the education process must be able to provide the best performance so that the education process runs as expected. This brings about the importance of improving the quality of educators and educational personnel that is adjusted to the demands and progress of the times. Sadly, this has not yet been fully carried out by educational policy-makers. Improving the quality of educators and educational personnel is mostly done without a through comprehensive analysis. This study aimed to develop a strategic planning as an effort to improve the quality of educators and educational personnel based on an analysis of the internal and external conditions of the school. This research was a qualitative study conducted at a vocational high school in West Java. Participants were the school principal, vice-principals, and teachers. Data were collected through interviews and documents. Data were analyzed by presenting data, reducing data, and drawing conclusions. This study was conducted through FGDs and a SWOT analysis for determining positions and determining strategic issues. The results showed that the school's position was in quadrant I (with an aggressive strategy) which showed a potential position to develop. This study recommends that several steps can be used to improve the quality of educators and educational personnel.